ANTIDIABETIC ACTIVITY OF CAFFEIC ACID AND 18Î’-GLYCYRRHETINIC ACID AND ITS RELATIONSHIP WITH THE ANTIOXIDANT PROPERTY - MOHAMMED, FATEN ZAHRAN; AL-HUSSAINI, AYMAN SALAH EL-DEEN; EL-SHEHABI, MOHAMMED EL-SAYED (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study was performed to investigate the antidiabetic effect of caffeic acid and 18 Î² -glycyrrhetinic acid against diabetic rats. Methods: In this experiment, the animals were divided into five groups. Group I: Normal rats. Group II: diabetic control rats.Group III: diabetic rats treated with 18Î²-glycyrrhetinic. Group IV: diabetic rats treated with caffeic acid. Group V: diabetic rats treated with 18Î²-glycyrrhetinic and caffeic acid. Fasting blood glucose, insulin, glutathione reductase (GR), glutathione peroxidase (GPx), total antioxidant (TAO), catalase , and superoxide dismutase (SOD) and malondialdehyde (MDA) were analyzed. Results: Fasting blood glucose and MDA were significantly increased, whereas insuline, GR, GPx, TAO, catalase , SOD were decreased significantly in diabetic rats. Though the diabetic rats treated with caffeic acid and 18Î²-glycyrrhetinic acid individual exerts beneficial effects in all the biochemical parameters in diabetic rats. The combined treatment with caffeic acid and 18Î²-glycyrrhetinic acid normalized all the above-mentioned biochemical parameters in diabetic rats. Conclusion: our findings demonstrated that 18Î²-glycyrrhetinic acid and Â caffeic acid either used individually or in combination to diabetic rats have an antidiabetic effect and a good antioxidant property .From the results, the combined dose of 18Î²-glycyrrhetinic acid and caffeic acid to diabetic rats showed promising antidiabetic effect and antioxidant property compared to individual treatments. Keywords: Diabetes, Caffeic acid, 18Î²-glycyrrhetinic acid, Streptozotocin, Antioxidant.